Pathophysiology, Diagnosis, and Management of Coronary No-Reflow Phenomenon - Kaur, Gagan; Baghdasaryan, Patrick; Natarajan, Balaji; Sethi, Prabhdeep; Mukherjee, Ashis; Varadarajan, Padmini; Pai, Ramdas G. (International Journal of Angiology, 2022)
Coronary no-reflow phenomenon is a lethal mechanism of ongoing myocardial injury following successful revascularization of an infarct-related coronary artery. Incidence of this phenomenon is high following percutaneous intervention and is associated with adverse in-hospital and long-term outcomes. Several mechanisms such as ischemia-reperfusion injury and distal microthromboembolism in genetically susceptible patients and those with preexisting endothelial dysfunction have been implicated. However, the exact mechanism in humans is still poorly understood. Several investigative and treatment strategies within and outside the cardiac catheterization laboratory have been proposed, but they have not uniformly shown success in reducing mortality or in preventing adverse left ventricular remodeling resulting from this condition. The aim of this article is to provide a brief and concise review of the current understanding of the pathophysiology, clinical predictors, and investigations and management of coronary no-reflow phenomenon.
Keywords: no-reflow phenomenon; cardiac MRI; angiogram; myocardial blush score; diagnosis; treatment; management